Reflection of Power Relations Inequality in The Domestic and Community Sphere Perspective Review of Criminal Law Protection Against Domestic Violence - Aida Dewi; Anang Setiyana (Universitas Islam Sultan Agung, 2026)
Violence against women in Indonesia continues to show an increasing trend despite various legal instruments that have been established, including the PKDRT law and the TPKS law. This phenomenon confirms the ineffectiveness of the legal system in providing comprehensive protection for women as a vulnerable group. The failure lies not only in the implementation aspect, but also rooted in the inequality of patriarchal-based power relations that affect the legal substance, institutional structure, and legal culture of society. In the context of criminal law, the purpose of punishment, whether retaliation, prevention, or rehabilitation, is not optimally achieved because the law still reflects social biases that place women in a subordinate position. This study uses normative legal research methods with legislation, conceptual, and comparative approaches. The Data were analyzed through an analysis of the concept of primary rules and secondary rules, and associated with the reality of patriarchy in law enforcement practice. This study also compared Indonesia's legal system with several countries to see the extent to which the reform of the substance, structure, and legal culture affect the effectiveness of Victim Protection. The results showed that the enforceability of criminal law in Indonesia is weakened due to the substance of the law that has not been gender responsive, biased law enforcement structure, and legal culture that still normalizes violence. Primary rules lose social power, while secondary rules do not function consistently in enforcement proceedings. Thus, legal reform is needed that focuses not only on regulatory changes, but also on the transformation of institutional perspectives and legal culture in order to realize a gender-fair sentencing system and effectively protect women.